International collaboration leading to high citations: global impact or home country effect? - Wang, Jue (2024)
Scientific research has become more collaborative, which brings a number of advantages including higher citation rates. This study examines the factors contributing to higher citations by distinguishing between the quality of work and the home country effect. Using international co-authorship as a key variable, we analyze citation patterns across a diverse range of fields over a 10-year period, and differentiate between citations accrued in the authors’ countries and citations received in other countries. The results demonstrate the presence of both global impact and a home country effect. Specifically, publications with international co-authorship receive significantly more citations from abroad, which strongly implies that international collaboration fosters high quality research and positively impacts citation rates, especially when considering the relatively smaller foreign community size once the authors’ home countries are excluded. On the other hand, it is also observed that domestic citations from authors’ countries increase faster than foreign citations and the effect is more pronounced over a longer period of time, which suggests that home country effect plays an important role in accumulating citations through the increased visibility in the domestic research community. The study confirms the pivotal role of international collaboration in research impact and highlights the significance of network building.